Current Research in the Interaction of Light and Matter: Implications for Future Technology - Ling Barra; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2024)
The interaction between light and matter is a fundamental topic in physics that has broad implications for developing new technologies. With the development of nanotechnology and photonics, a deeper understanding of how light can be affected by and affect matter at the micro and nano scales has become important. This research aims to explore and characterize the interaction of light with matter under various experimental and theoretical conditions to reveal new phenomena that can be exploited in future technologies, such as in the development of quantum computers, advanced sensors, and optical communication systems. This research uses a combination of experimental methods and computer simulation. The experiments were carried out using advanced spectroscopy and microscopy techniques to observe interactions at the atomic and molecular levels. Computer simulations are used to model interactions and predict the behavior of materials under the influence of different light. The results show that by manipulating the structure of materials at the nanoscale, we can significantly change the way materials interact with light. This includes creating meta-material effects not found in nature, which allow the control of light in a highly efficient and selective manner. This study's conclusions confirm that the potential for controlling and exploiting light in technological applications has been substantially expanded through high-precision manipulation of materials at the nanoscale. These findings pave the way for the development of various advanced technological applications that are more efficient and effective, providing a strong foundation for future technological innovations that rely on the interaction of light and matter.